Observation of an Atypical Hairless Free-Ranging Individual of Grivet Monkey (Chlorocebus aethiops), at Wondo Genet Patch of Forest, Southern Ethiopiaorocebus aethiops) at Wondo Genet forest in Ethiopia, East Africa. - Mamo, Yosef; Alemu, Yitayal; Asefa, Addisu (Journal of Forestry and Natural Resources, 2025)
This study documents the observation of a highly unusual hairless female grivet monkey (Chloro- cebus aethiops) at Wondo Genet College of Forestry and Natural Resources Campus, Ethiopia,a phenomenon not previously documented in free-ranging populations in the region. Follow- ing an initial report from local community members of a “strange looking” monkey, systematic field observations were conducted over a six-month period at two-week intervals to assess the individual’s morphology, behavior, and interactions with conspecifics. The monkey displayed almost complete hairlessness, except for a small tuft on the tail, and weighed approximately1.5 kg, substantively less than typical adults. Additionally, irregular white patches of depig- mentation were present on the upper left flank, with no signs of dermal irritation or lesions. Behavioral observations revealed distinctly atypical foraging and social patterns. Unlike other troop members, the individual primarily foraged near office and training areas, avoided res- idential zones, and rarely engaged in grooming or close social interactions. Other monkeys initially avoided it, though selective tolerance from one adult male was occasionally noted. The hairless individual exhibited thermoregulatory behaviors, such as lying on sun-warmed rooftops during cooler mornings, presumably to mitigate cold stress due to the absence of fur. The findings suggest that common causes of hair loss, including infection, nutrition, stress, or over-grooming, are implausible explanations. Instead, hairlessness likely stems from an under- lying genetic mutation or immunological dysfunction. This case underscores the importance of detailed documentation of rare morphological anomalies in wild primates; as these condi- tions may influence individual survival, social integration, and adaptive behaviors within both natural and human-modified environments.